Garment failure causes and solutions: Slowing the cycles for circular fashion. (1st June 2022) - Cooper, Tim; Claxton, Stella
Abstract: Clothing consumption continues to increase worldwide, with many fashion brands facing criticism for producing poor quality garments which have short lifetimes, adding to already unsustainable levels of post-consumer waste. This paper aims to identify the causes of failure for different types of garments and discusses solutions through which to increase their durability. Recent literature has highlighted the need for companies in the clothing industry to progress to a circular fashion model and the important role of consumer attitudes and expectations in determining clothing lifetimes. Garment failure due to inadequate technical durability is acknowledged but has not attracted significant attention from academic researchers. This paper reports on a survey which identified different types of garment failure by assessing discarded items at end of life, explains the causes of such failure and reveals potential solutions, drawing upon data from a series of research projects commissioned by WRAP and Defra. The survey revealed that the most common causes of garment failure are pilling and colour fading. Other causes included fabric breakdown, accidental damage, loss of dimensional stability, logo failure, discolouration, and holes in seams. Increased garment durability is achievable by following best practice technical guidance but also requires effective management of product development and manufacturing processes. Implementation of technical solutions requires appropriate testing, improved technical skills and knowledge, collaboration to promote better design practices, and new business models that support garment longevity. Highlights: Clothing consumption continues to increase and is unsustainable. The lifetime of many garments is unduly short due to inadequate technical quality. A garment condition survey identified the most common causes of failure as pilling and colour fading. Causes of failure and potential solutions were explored through a multi-methods research approach. Solutions include better testing, improved technical expertise, collaboration on design, and sustainable business models.